Effects of Virtual Reality Education on Procedural Pain and Anxiety During Venipuncture in Children: A Randomized Clinical Trial - Ryu, Jung-Hee; Han, Sung-Hee; Hwang, Sang Mee; Lee, Jiyoun; Do, Sang-Hwan; Kim, Jin-Hee; Park, Jin-Woo (Frontiers in Medicine, 2022)
Background: Venipuncture is one of the most frequent and frightening medical procedures for children. This randomized clinical trial aimed to evaluate whether pre-procedural immersive virtual reality (VR) education could decrease pain and anxiety during venipuncture procedure of children. Methods: Sixty children scheduled for venipuncture at the phlebotomy unit were randomized into either the control or VR group. Before the procedure, children of the control group received conventional simple verbal instructions, whereas those of the VR group experienced a 4-minute VR education regarding venipuncture. The primary outcome was the pain and anxiety of pediatric patients assessed with the children’s hospital of eastern ontario pain scale. Secondary outcomes were parental satisfaction, venipuncture time, repeated procedure and procedural difficulty rated by phlebotomists. Results: The pain and anxiety score during the procedure was significantly lower in the VR group than in the control group (median [IQR], 6.0 [5.0 – 7.0] vs. 8.0 [6.0 – 9.8], P = 0.001). Parental satisfaction about the procedural process were higher in the VR group than in the control group (P = 0.029), and the degree of procedural difficulty was lower in the VR group, compared to the control group (P = 0.026). Conclusion: The preprocedural VR education significantly reduced pain and anxiety of children and decreased the procedural difficulty of phlebotomists during venipuncture procedure.